A Syndemic Perspective on the Management of Non-communicable Diseases Amid the COVID-19 Pandemic in Low- and Middle-Income Countries - Uday Narayan Yadav; Uday Narayan Yadav; Binod Rayamajhee; Binod Rayamajhee; Sabuj Kanti Mistry; Sabuj Kanti Mistry; Shradha S. Parsekar; Shyam Kumar Mishra; Shyam Kumar Mishra (Frontiers Media S.A., 2020)
The global coronavirus disease (COVID-19) pandemic has greatly affected the lives of people living with non-communicable diseases (PLWNCDs). The health of PLWNCDs worsens when synergistic epidemics or "syndemics" occur due to the interaction between socioecological and biological factors, resulting in adverse outcomes. These interactions can affect the physical, emotional, and social well-being of PLWNCDs. In this paper, we discuss the effects of the COVID-19 syndemic on PLWNCDs, particularly how it has exposed them to NCD risk factors and disrupted essential public health services. We conclude by reflecting on strategies and policies that deal with the COVID-19 syndemic among PLWNCDs in low- and middle-income countries.